Sistem Pakar Mendiagnosa Penyakit Anemia Berbasis Web Menggunakan Metode Teorema Bayes - Siti Nur Indah Fauziah; Agung Wijoyo (CV. Multi Kreasi Media, 2024)
The Bayes theorem method in which this method builds a system that works by calculating probabilities based on the symptoms experienced by the patient. This expert system is designed using the programming language php, html and MySQL as the database. The results of this study are able to diagnose anemia suffered by patients and are able to provide solutions to the disease. This study aims to make it easier for the community to deal with anemia without having to come in line to the health center and to be able to provide accurate analysis results regarding the handling of anemia easily and quickly. Therefore a website application was designed to diagnose anemia using the Bayes theorem method. The Bayes theorem method in which this method builds a system that works by calculating probabilities based on the symptoms experienced by the patient. This expert system is designed using the programming language php, html and MySQL as the database. The results of this study are able to diagnose anemia suffered by patients and are able to provide solutions to the disease.